Podcastes no Museu do cotidiano: um estudo sobre conteúdos sonoros e diálogos abertos - Marcela de Queiroz Teófilo (2019)
In this research, a philosophy teacher seeks to share her experience about her expertise in curatorship, while she was in a research in the Professional Master Course in Education and teaching (PROMESTRE/FAE/UFMG). This opportunity culminated the production of six episodes from the initial "soundtrack" DecolActive Podcast to the Museu do Cotidiano (MuC), in Belo Horizonte, Minas Gerais. Therefore, areas like philosophy, education, communication, literature and museology talk among themselves when it refers to the language and the different ways to know curatorship experiences lived by philosophers, educators, journalists, poets and museologists, among others. The pedagogic and philosophic method or systematization, for instance, receive a phenomenon approach, which the comprehension relates to the working from the society, where they're identified. For this reason, we propose a dialogue with different thinkers when it refers to the role of each person in his attitudes towards to the information and the construction, the knowledge socialization. The qualitative epistemology, as a methodological and epistemological reference helped the audio captation during the visits at the mUc. It also contributed to the immersion of the theoretical basis, analyzing the exhibition scenario. Ideas and concepts identified in the space and the narrative mediation offered by Antonio interposition were determinant to the recordings edition. Thus, the resonant contents are presented in consonance with the elements from the research movement (auto) biographical, from Educommunication and with the representative images from the "Narrator", by W. Benjamin and from "Subject of experience", Larrosa. The intersubjectivity from the dialogue and communicative actions presented in the Paulo's Freire and Habermas' thoughts are determinants to the obtained results. While they are in digital shape, the podcast requires the continuity and stimulates the presence from the mUc in the virtual spaces, where the people from the century XXI amplify their convivial horizons, narrate, register and share their daily experience. Therefore, to edit the recorded audios, the collaboration of the visitors comments was in the reflection of the successive hypothesis, and it also involved the identification and indicators organization (a group of typical idiomatic expressions, surprised and happiness traits and emotions in the visiting to the mUc) in title category " the childhood cultivation", "Mandatory stops" and "Tragicomedies from the singularity". For diverse circumstances, when integrated, intersubjectivities, languages and media involve multiple characteristics, resources and functions which are possible to the people. In the interaction among the diversities, the voices recorded during the elaboration collaborate, so that the conceptions find and reverberate the opened dialogues at mUc. The invitation to daily researches to get the own and constant development involving free, individual and collective shapes about producing and reproducing contents in our society: the creation of products and the educational actions shimmered also represented an initiative to promote the education development/ philosophy divulgation in non-formal education environments as cafes, museums, cultural center, squares, parks, public equipments, media/digital platforms, etc.